249. Assessing of a Dual flip Angle technique (DFA) for 3D T1 mapping in clinical quantitative MRI. (December 2018) - Busoni, S.; Colagrande, S.; Di Stasio, M.; Noferini, L.
Abstract : Purpose: Liver T1 mapping has shown as a promising diagnostic tool for cirrhosis diagnosis[1] . The aim of this study is to assess the accuracy of a 3D dual flip angle (DFA) T1 mapping technique[2] with whole liver coverage before and after contrast medium injection (CMI). Methods: DFA technique has been evaluated on a uniform phantom, to investigate measured T1 spatial changes with respect to distance from isocenter, and on a phantom containing multiple certified T1 value gel tubes, in order to assess accuracy over a wide range of clinical T1 values. 1.5T MRI scanner was used. A software code was specifically developed to generate T1 maps in DICOM format. In Table 1 the nominal and measured tube T1 values are reported for comparison. The technique has been applied to patients (n = 80 since 2016) undergoing abdominal exams for liver diseases. Three gel tubes, with T1 spanning over the clinical values range, are fixed on patient abdomen during acquisition, in order to check measurement accuracy (see Fig. 1 showing T1 map of a patient with the three tubes). DFA sequence takes into account optimal FAs for pre/post CMI. Relative T1 variation between pre/post CMI (ΔT1%) are measured. Results: B1 spatial inhomogeneity effect can approach ∼20% of the nominal T1 value, at 10 cm from isocenter. The T1 accuracy within 5 cm from the isocenter is better than 10% over the range 200 up to 1500 ms. T1 values measured on the tubes placed on patients are consistent with their nominal values after correction for distance from isocenter, and do not significantly vary during the exam. Conclusions: The technique has shown to be reliable and robust. A correction for B1 spatial inhomogeneity might be needed if the volume to be mapped extend more than 10 cm from the isocenter. In order to check significant differences between normal and cirrhotic livers, T1 variations due to CMI can be measured in clinical cases with this technique with an accuracy of about 10%.